Clinical and Diagnostic Significance of Lactate Dehydrogenase and Its Isoenzymes in Animals - Robert Klein; Oskar Nagy; Csilla Tóthová; Frederika Chovanová (Veterinary Medicine International)
Lactate dehydrogenase (LDH) is widely distributed enzyme in cells of various living systems where it is involved in carbohydrate metabolism catalyzing interconversion of lactate and pyruvate with NAD+/NADH coenzyme system. Cells of tissues are direct source of lactate dehydrogenase isoenzymes that are naturally distributed in blood plasma/serum of animals and humans producing characteristic profile. This profile depends on intracellular isoenzyme concentration in all tissues that contribute to the common pool of lactate dehydrogenases in plasma/serum as a consequence of natural cell degradation. LDH is widely distributed in the body, high activities are found in the heart, liver, skeletal muscle, kidney, and erytrocytes, whereas lesser amounts are found in the lung, smooth muscle, and brain. Because of its widespread activities in numerous body tissues, LDH is elevated in a variety of disorders. There are many conditions that contribute to increased activity of LDH. An elevated total LDH value is a rather nonspecific finding. Therefore, LDH assays assume a more clinical significance when separated into isoenzyme fractions. The activity of LDH and its serum and tissue patterns and composition show great variations between the species. These differences do not allow using catalytic activities of LDH isoenzymes from one species to another. Instead, the pattern of serum LDH isoenzymes should be interpreted in respect to its species origin that is important in particular in veterinary medicine. Determination of total LDH activity and its isoenzyme pattern in serum of mammals had become one of the biochemical indicators in the assessment of organ disorders. When the content of cells is released from tissue to plasma, as on cell injury, the LDH isoenzyme pattern of the serum changes in favour of the profile of the affected organ (tissue) that can be used in the diagnostic practice.